Linguculturological Interpretation and Study of the Concept "Vatan (Homeland)" in German and Uzbek Languages - Hayotova Dilafroz Zoyirovna (Indonesian Journal of Innovation Studies, 2022)
This article is about linguistics, a new direction in linguistics of cultural studies, the concept and the interpretation of the concept of the motherland in Uzbek and Russian. It also gives an idea of the theoretical views of conceptual scientists.